Oral communications of speech language pathologists in a clinical setting - Koran, Leela (Journal of Modern Languages, 2017)
This paper reports on a study that attempts to describe the oral communication of Speech-Language Pathologists (SLP) in a clinical setting within a multicultural society and addresses, to some extent, the problem of lack of research on SLP practice in Malaysia.